Services for data integration - Catharina Riedemann; Christian Timm (Data Science Journal, 2003)
The fact that many decisions need a combination of information sources makes easy integration of geospatial data an important data usability issue. Our vision is to achieve automated just-in-time integration. As a foundation, we present a system architecture with distributed data and services. Existing and evolving standards and technologies fitting into this architecture are presented along with their scope and shortcomings. A major point is the appropriate definition of data and operation semantics. Further research is needed here to make the automatic formation of service chains for data integration possible.